2020
DOI: 10.1007/s00701-020-04222-y
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of cisternostomy as adjuvant to decompressive craniectomy for the management of severe brain trauma

Abstract: Objective To evaluate the value of an adjuvant cisternostomy (AC) to decompressive craniectomy (DC) for the management of patients with severe traumatic brain injury (sTBI). Methods A single-center retrospective quality control analysis of a consecutive series of sTBI patients surgically treated with AC or DC alone between 2013 and 2018. A subgroup analysis, "primary procedure" and "secondary procedure", was also performed. We examined the impact of AC vs. DC on clinical outcome, including long-term (6 months)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 35 publications
2
34
0
Order By: Relevance
“…15 Giammattei et al in a study of 40 cases showed that implementation of cisternostomy as adjuvant to decompressive craniectomy had lower ICP values and better outcomes when compared with craniectomy alone. 16 In our study, patients with average low ICP after cisternostomy (5.71 AE 1.60 mm Hg) had good outcome at 3 months follow-up. Patients with high average ICP after cisternostomy (7.25 AE 1.39 mm Hg) had poor outcome.…”
Section: Intracranial Pressuresupporting
confidence: 48%
“…15 Giammattei et al in a study of 40 cases showed that implementation of cisternostomy as adjuvant to decompressive craniectomy had lower ICP values and better outcomes when compared with craniectomy alone. 16 In our study, patients with average low ICP after cisternostomy (5.71 AE 1.60 mm Hg) had good outcome at 3 months follow-up. Patients with high average ICP after cisternostomy (7.25 AE 1.39 mm Hg) had poor outcome.…”
Section: Intracranial Pressuresupporting
confidence: 48%
“…Giammattei et al performed a retrospective study in severe TBI patients comparing DC ( n = 22) with DC + CS ( n = 18). 15 The groups were comparable with respect to age and GCS at presentation, but the DC + CS group had more patients with unilateral pupillary dilation (55 vs. 36%) and higher average Rotterdam CT score (4.7 vs. 3.8; p = 0.03). The decision to add CS to DC was based on the availability of surgeon skilled in vascular and skull base approaches, which can be a source of introducing selection bias.…”
Section: Discussionmentioning
confidence: 80%
“…However, as people often attach importance to life rescue while neglecting functional rehabilitation, the disability rate is greatly increased, and most of the surviving patients will leave behind varying degrees of disability. In addition to cognitive dysfunction, language dysfunction, and physical function accounted for a large part [ 20 ]. In the United States, some scholars published the meta-analysis report “early rehabilitation based on evidence: recommendations for Clinical practice” from 1999 to 2000.…”
Section: Discussionmentioning
confidence: 99%